This answer is restricted. Please login to view the answer of this question.

Login NowSolution:

Given series is

\(\sum_{n=1}^{∞} \frac{(x – 3)^n}{x}\) …. (i)

comparing it with \(\sum_{n=1}^{∞} u_n\) then

\(u_n = \frac{(x – 3)^n}{x}\) ….. (ii)

Here

\(\lim_{n\rightarrow ∞} \left [ \frac{(x – 3)^{n+1}}{x} \times \frac{x}{(x – 3)^n} \right ]\)

\(= \lim_{ n \to ∞} (x – 3) \)

= x – 3

By D’Alembert ratio test the given series is convergent for

\(\left | x – 3 \right | < 3 \enspace\enspace\enspace i.e. \enspace\enspace -1 < (x – 3) < 1\)

= 2 < x < 4

and is divergent for \(\left | x – 3 \right | > 1\)

And further test is needed for \(\left | x – 3 \right | = 1\) i.e. at x = 2 and x = 4

At x = 2, the series (i) becomes,

\(\sum_{n=1}^{∞}(u_n) = \sum_{n=1}^{∞} \frac{(-1)^n}{2}\)

And is an alternative series. Comparing it with \(\sum_{n=1}^{∞} (-1)^n \enspace V_n\) then

\(V_n = \frac{1}{2}\)

Here

\(\lim_{n \to ∞} V_n = \lim_{b \to ∞}\left ( \frac{1}{2} \right ) = \frac{1}{2} \neq 0\)

So, the given series is divergent at x = 2, by Leibnitz test.

And at x = 4, the series (i) becomes

\( = \sum_{n=1}^{∞} (u_n) \)

\(= \sum_{n=1}^{∞} \left ( \frac{1}{2} \right )\)

\(= \left ( \frac{1}{2} \right ) \sum_{n=1}^{∞} (1)\)

= ∞

This means the given series is divergent at x = 4

Thus the given series is convergent only for 2 < x < 4

If you found any type of error on the answer then please mention on the comment or report an answer or submit your new answer.

Click here to submit your answer.

HAMROCSIT.COM

## Discussion